Pengaruh Kualitas Pelayanan dan Brand Image Terhadap Keputusan Konsumen Memilih Triple E Event Bali Sebagai Penyelenggara Mice & Event - Aditya, I Made Ivan; Citrawati, Luh Putu; Arjaya, Ketut (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
The purpose of this research was to determine the effect of service quality (X1) and brand image (X2) on consumer decisions (Y). The population in this study were consumers of Triple E Event Bali, with 95 respondents as a sample. The data collected were subjected to Multiple Linear Regression, Coefficient of Determination, calculation of Effective Contribution, t-test and F-test. T-test on the effect of service quality (X1) found the value of t count > t table (5,695 > 1,986). This shows that service quality (X1) has a significant positive effect on consumer decisions (Y), brand image has a significant positive effect on consumer decisions (Y) Based on t-test on brand image (X2), it appeared that t count > t table (4,956 > 1,986). That means the brand image (X2) has a significant positive effect on consumer decisions (Y). F test obtained F count > F table (84,169 > 3,10) which means service quality (X1) and brand image (X2) simultaneously have a significant positive effect on consumer decisions. Based on Coefficient of Determination tetst (R2), it is known that the variables of service quality (X1) and brand image (X2) simultaneously influence consumer decisions (Y) by 64.7%. The results of the effective contribution calculation showed that the service quality (X1) has a contribution of 35% to consumer decisions (Y) and the brand image variable (X2) has a contribution of 29.7% to consumer decisions (Y).